Analysis and simulation of reverse osmosis equipment: Case of La Guajira, Colombia. (March 2023) - Serrano-Florez, Dario; Florez, Whady Felipe; Bustamante, Carlos Andres; Chejne, Farid
Abstract: Energy resources and potable water are important assets for every country. Electric power produced from renewable sources can be used to provide water desalination systems and meet the energy needs of populations living in isolated and remote areas. This study models and simulates a reverse osmosis (RO) water desalination system using dynamic mathematical models in one dimension, and applies it to water sources from the department of La Guajira, Colombia. Most of the indigenous communities are concentrated in the upper and middle areas of that region, where there are brackish water sources such as groundwater wells that could undergo water purification to improve community's quality of life. Furthermore, these areas have the best solar radiation potential in Colombia. The Yuyurupana indigenous community was chosen for the study; they are located in the rural area of the municipality of Maicao. This place has a groundwater well with 3055.77 mg/L of total dissolved solids (TDS) and average solar radiation of 4.8 kWh/m 2 /month. At a feed pressure of 11.65 atm, the system obtained a permeate concentration quality of 317.45 mg/L, which is below the maximum allowable according to the Colombian Ministry of Environment. The specific energy consumption (SEC) was calculated and yielded a value of 0.644 kWh/m 3 . It requires 152 photovoltaic solar panels and a total area of 294.9 m 2 to supply electricity to the system. The mathematical models were validated by comparing results with those of previous studies found in the literature. Highlights: A reverse osmosis model used is solved numerically. A dynamical model with variable physical properties is used. Numerical solution by the lines method and implicit Radau solver is used. The model results will be applied in an indigenous community. Solar energy consumption is included in the reverse osmosis calculations.